The Old Vs. New Indian Culture in Anita Desai’s In Custody - Abdullatif, Noor Isa; Taher, Isra Hashim (Al-Adab Journal, 2022)
Anita Desai (1937- ) is a contemporary Indian novelist, short story, and children’s books writer. She introduces psychological novels to India. Her works are highly symbolic. In her novels, she discusses cultural themes like the clashes of Eastern and Western cultures and the conflicts between Indian cultures and religions. In In Custody (1984), she discusses many cultural themes focusing on the death of the old valuable culture of India after Partition and the birth of a new culture. In In Custody (1984), Desai depicts the changes that India has witnessed in post-colonial period. She focuses on the ruined ancient Indian culture which has been replaced by a new materialistic one at the hands of the British colonization. She concentrates on the death of art and poetry specially the death of Urdu poetry and language which are associated with the glorious culture once India had in the past. Deven, the protagonist, whose ambition is to be a great poet in Urdu is forced to teach Hindi instead of Urdu which is rarely used. The novelist narrates the journey of Deven who struggles to revive Urdu poetry by interviewing the famous Urdu poet, Nur. Deven faces many obstacles during his journey. These obstacles are represented in the change India has witnessed and in the change of people’s motives and mentality. The paper discusses the influence of the Partition and the British colonialism on the Indian culture and the change India witnessed due to the Partition between Muslims and the Hindus.